Similarity solutions for thawing processes with a convective boundary condition - Ceretani, Andrea Noemí (2014)
An explicit solution of similarity type for thawing in a saturated semi-infinite porous media when change of phase induces a density jump and a convective boundary condition is imposed at the fixed face, is obtained if and only if an inequality for data is verified. Relationship between this problem and the problem with temperature condition studied in [8] is analized and conditions for physical parameters under which the two problems become equivalents are obtained. Furthermore, an inequality to be satisfied for the coefficient which characterizes the free boundary of each problem is also obtained.